2006
DOI: 10.1158/1078-0432.ccr-05-1886
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumor-Infiltrating CD4+ T-Cell Subpopulations in Head and Neck Cancers

Abstract: Purpose: CD4 + T cells play a central role in initiating and maintaining anticancer immune responses. However, regulatory CD4 + CD25 + T cells which express Foxp3 have also been shown to inhibit antitumor effector T cells. In view of these heterogeneous CD4 + T-cell populations, this study was designed to determine the prognostic value of various tumor-infiltrating CD4 + T-cell populations in head and neck squamous cell carcinoma. Experimental Design: Eighty-four newly diagnosed untreated patients with histolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
396
6
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(450 citation statements)
references
References 52 publications
30
396
6
12
Order By: Relevance
“…Our results suggest that beyond LOH, our gene expression-based classification of OPL may provide an opportunity to refine the molecular assessment of oral cancer risk. Consistent with previous observations in HNSCC, 4951 we found that premalignant-infiltrating T-cells and monocytes are associated with a lower oral cancer risk, suggesting an important role of these populations during oral carcinogenesis. Scattered evidence on the biology of OPL suggests the presence of an immune stimulatory environment characterized by IFN-gamma, and other pro-inflammatory cytokines and immune cells, including NK cells, macrophages and activated CD8 + T-cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that beyond LOH, our gene expression-based classification of OPL may provide an opportunity to refine the molecular assessment of oral cancer risk. Consistent with previous observations in HNSCC, 4951 we found that premalignant-infiltrating T-cells and monocytes are associated with a lower oral cancer risk, suggesting an important role of these populations during oral carcinogenesis. Scattered evidence on the biology of OPL suggests the presence of an immune stimulatory environment characterized by IFN-gamma, and other pro-inflammatory cytokines and immune cells, including NK cells, macrophages and activated CD8 + T-cells.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, Foxp3 þ cells were analysed by immunohistochemistry in order to evaluate T regs in gastric cancer. Previous studies in human malignancies reported that the prevalence of T regs defined as a CD4 þ CD25 þ population was significantly increased in TILs compared to the normal counterparts (Woo et al, 2001;Liyanage et al, 2002;Ormandy et al, 2005;Badoual et al, 2006;Petersen et al, 2006). Furthermore, the high prevalence of CD4 þ CD25 þ T regs is closely associated with a poor prognosis in ovarian (Curiel et al, 2004) or pancreatic (Liyanage et al, 2002) cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, in humans, many studies have revealed that the population of T regs in tumour-infiltrating lymphocytes (TILs) is significantly larger than in normal tissues in several malignancies (Woo et al, 2001;Liyanage et al, 2002;Ormandy et al, 2005;Badoual et al, 2006;Petersen et al, 2006). We have reported that the frequency of T regs among TILs, tumourdraining regional lymph nodes, and peripheral blood lymphocytes is higher in gastric and oesophageal cancer patients than that in their normal counterparts (Ichihara et al, 2003).…”
mentioning
confidence: 99%
“…In agreement with this hypothesis, higher numbers of tumour-infiltrating T reg were shown to be associated with poor outcome in pancreatic [25] and hepatocellular [27] carcinomas. In follicular lymphoma, head and neck, and ovarian cancer the number of infiltrating FOXP3 + immune cells has shown to be an independent prognostic factor [47][48][49]. However, studies of other tumours have led to conflicting results.…”
Section: Discussionmentioning
confidence: 99%